2014
DOI: 10.1177/1062860614541291
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Severe Sepsis via Electronic Surveillance

Abstract: An electronic sepsis surveillance system (ESSV) was developed to identify severe sepsis and determine its time of onset. ESSV sensitivity and specificity were evaluated during an 11-day prospective pilot and a 30-day retrospective trial. ESSV diagnostic alerts were compared with care team diagnoses and with administrative records, using expert adjudication as the standard for comparison. ESSV was 100% sensitive for detecting severe sepsis but only 62.0% specific. During the pilot, the software identified 477 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…For example, in a prospective pilot study, Buck 39 noticed that 40% of the patients identified by the alert received escalated care in the form of repeated evaluation by a physician, additional medications or intravenous fluids, laboratory tests, respiratory support, or transfer to the ICU. Additionally, in the pilot study mentioned earlier, Brandt et al 36 showed that the alert resulted in a diagnosis of sepsis approximately 27 minutes earlier when compared with the time of sepsis diagnosis based on chart review. In a before and after interventional study, Kurczewski et al 40 evaluated a tool that used at least two SIRS criteria to trigger the sepsis alert but modified it so that one of them had to include an abnormal WBC count or temperature.…”
Section: Sirs-based Screening Toolsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in a prospective pilot study, Buck 39 noticed that 40% of the patients identified by the alert received escalated care in the form of repeated evaluation by a physician, additional medications or intravenous fluids, laboratory tests, respiratory support, or transfer to the ICU. Additionally, in the pilot study mentioned earlier, Brandt et al 36 showed that the alert resulted in a diagnosis of sepsis approximately 27 minutes earlier when compared with the time of sepsis diagnosis based on chart review. In a before and after interventional study, Kurczewski et al 40 evaluated a tool that used at least two SIRS criteria to trigger the sepsis alert but modified it so that one of them had to include an abnormal WBC count or temperature.…”
Section: Sirs-based Screening Toolsmentioning
confidence: 97%
“…35 Several studies have investigated the diagnostic accuracy of SIRS-based screening tools (Table 2). In a prospective pilot study, Brandt et al 36 required the presence of infection, organ dysfunction, or altered mental status in the patient's active problem list prior to allowing an automated system to search for SIRS criteria. The alert was issued to a sepsis surveillance group consisting of an intensivist and critical care nurse, who performed a chart review to determine if the primary team should be notified.…”
Section: Sirs-based Screening Toolsmentioning
confidence: 99%
“…Previous studies have shown that ICD-9 diagnosis codes for severe sepsis and septic shock provide a lower sensitivity for detection of such conditions (22,23,24). In one study, 48.4% of patients meeting clinical criteria for severe sepsis were not assigned a diagnosis code for severe sepsis (22).…”
Section: Limitationsmentioning
confidence: 99%
“…In one study, 48.4% of patients meeting clinical criteria for severe sepsis were not assigned a diagnosis code for severe sepsis (22). Also, patients identified with a diagnosis code tend to be septic patients with more severe illness (23,24).…”
Section: Limitationsmentioning
confidence: 99%
“…Automated systems for early diagnosis of sepsis using clinical-and laboratory-based data have been widely studied in the literature [7]- [11]. Through development of electronic health records and electronic surveillance systems for healthcare systems, a number of studies have evaluated models for automated sepsis detection and their effectiveness [7], [8], [10], [12], [13]. The studies mostly proposed automated systems of evaluating clinical data for prediction of sepsis using different machine learning algorithms such as support vector machine, k-nearest neighbor, decision trees, regression trees, random forests, logistic regression and lazy Bayesian rules [7], [10]- [12].…”
Section: Introductionmentioning
confidence: 99%